2018
DOI: 10.3168/jds.2017-12551
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Does early-life administration of a Megasphaera elsdenii probiotic affect long-term establishment of the organism in the rumen and alter rumen metabolism in the dairy calf?

Abstract: Megasphaera elsdenii is a bacterial species of the rumen that can utilize lactate to produce butyrate, a key volatile fatty acid often implicated in driving calf rumen development. Because lactate is abundant in the rumen of young calves, administration of M. elsdenii to increase butyrate production and thus promote calf rumen development is an appealing possibility. The main objective of this study was to determine whether M. elsdenii administration to calves via oral drench at 14 d of age affected its long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Table 3 presents M. elsdenii abundance in the rumen of animals determined through these culture-independent methods [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Relative abundance (RA) in the rumen is typically well under 1% of the total bacteria, except in animals experiencing metabolic or production problems, particularly milk fat depression.…”
Section: Abundance In the Rumenmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 presents M. elsdenii abundance in the rumen of animals determined through these culture-independent methods [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Relative abundance (RA) in the rumen is typically well under 1% of the total bacteria, except in animals experiencing metabolic or production problems, particularly milk fat depression.…”
Section: Abundance In the Rumenmentioning
confidence: 99%
“…Muya et al [ 109 ] found that M. elsdenii NCIMB 41125 dosed at 14 days of age increased ruminal butyrate and plasma β-hydroxybutyrate (BHBA) and also improved both the intake of starter feed and ruminal development (measured as an increase in the absorptive area) compared with non-dosed calves. In the second study [ 41 ], Lactipro ® (2 × 10 8 cfu/mL of M. elsdenii NCIMB 41125) was administered to dairy calves and, although M. elsdenii shifted the abundance of certain less abundant bacteria, there was no increase in M. elsdenii abundance as well as no effect on ruminal and blood parameters.…”
Section: Nutritional Importancementioning
confidence: 99%
“…In addition, yeast products exhibit properties such as regulating intestinal balance, improving immunity, and enhancing animal production performance (Lu et al, 2022). Studies have shown that S. boulardii can maintain the micro-ecological balance of the rumen, thereby increasing milk yield and milk fat content in dairy cows (Yohe et al, 2018). There are currently many reports on the use of yeast and B. coagulans in livestock and poultry production.…”
Section: Introductionmentioning
confidence: 99%
“…Muya et al (2015) showed improved feed intake and rumen development, suggesting increased epithelium metabolism and improved absorption of digestive end products. Whereas, no effect was observed in another study using the same strain and a similar protocol (Yohe et al, 2018).…”
Section: Modulating the Gastrointestinal Microbiota In Young Ruminants For Health And Productionmentioning
confidence: 87%
“…Similarly, the best window(s) of age when the microbiota could be modulated have to be refined. Establishment of different populations might not be a single isolated event and a continuous exposure seems to be necessary for acquiring adult-like communities (Morgavi et al, 2015) or successfully engraft specific microbes (Yohe et al, 2018). A better definition of the role of early microbial communities on the host-microbiota dialogue and the regulation of the immune system is also important for this subject.…”
Section: Modulating the Gastrointestinal Microbiota In Young Ruminants For Health And Productionmentioning
confidence: 99%